Nordic Pioneers of Biodynamic and Organic Agriculture - Paull, John; Tutturen, Tord (European Journal of Development Studies, 2024)
Fifty Nordic pioneers of biodynamic (BD) agriculture, and hence of organic agriculture, are identified. These individuals, from Norway (n = 23), Sweden (n = 12), Denmark (n = 10), and Finland (n = 5), joined the Experimental Circle of Anthroposophical Farmers and Gardeners in the years 1924–1946. These pioneers comprised both men (n = 35) and women (n = 14), with one member of undetermined gender. The Experimental Circle was headquartered at the Goetheanum, Dornach, Switzerland. One of these pioneers (Anna Wager Gunnarson) attended the foundational course of biodynamic and organic agriculture, presented by Dr Rudolf Steiner (1861–1925), in eight lectures at Koberwitz (now Kobierzyce, Poland) in June 1924. The core element of the course was that agriculture was properly a biological rather than a chemical pursuit. The ‘Agriculture Course’ was subsequently issued (in German from 1926) as a subscriber-only published book to members (of the Anthroposophical Society) who joined the Experimental Circle. Each Circle member signed a non disclosure agreement (NDA) and committed to testing the ideas of the course. A milestone was the 1938 book by Ehrenfried Pfeiffer, ‘Bio-Dynamic Farming and Gardening,’ which arguably released Experimental Circle members from their NDA. Nordic members joined progressively over the two decades following the Koberwitz course, with new memberships peaking in 1932 (n = 7), and continuing through the years of World War II (WWII). Biodynamic agriculture is still practiced in the Nordic countries of these pioneers, with Denmark presently accounting for 2,998 hectares, Sweden 873 ha, Norway 548 ha, and Finland 384 ha. The Nordic countries have developed strong organic sectors, with Sweden accounting for 610 543 ha of certified organic agriculture (which is 20.2% of its agricultural land), Finland 315 112 ha (14.4%), Denmark 299 998 (11.4%), and Norway 45 181 ha (4.6%). Iceland has no identified BD pioneers, presently no BD hectars, and 6 440 ha of organic agriculture (0.4% of total agriculture ...